A diagnostic algorithm for assessment of liver fibrosis by liver stiffness measurement in patients with chronic hepatitis B. Issue 11 (12th May 2017) - Cai, Y.‐J.; Dong, J.‐J.; Wang, X.‐D.; Huang, S.‐S.; Chen, R.‐C.; Chen, Y.; Wang, Y.‐Q.; Song, M.; Chen, Y.‐P.; Li, Z.; Zhou, M.‐T.; Shi, K.‐Q.
Summary: Steatosis could affect liver stiffness measurement in patients with nonalcoholic fatty liver disease and chronic hepatitis C. In this study, we aimed to investigate the impact of steatosis on liver stiffness in hepatitis B virus (HBV)‐infected patients and develop a diagnostic algorithm for prediction of liver fibrosis by liver stiffness based on the controlled attenuation parameter. A total of 488 HBV‐infected patients who underwent clinical examination, Fibroscan and liver biopsy were prospectively enrolled. The best liver stiffness measurement (kPa) cut‐offs for significant fibrosis (S≥3) and advanced fibrosis (S≥4) were 8.1 and 10.9, respectively. The best controlled attenuation parameter cut‐off for severe steatosis (≥30%) was 287 dB/m. Among patients with low‐grade fibrosis (S0‐S2/S0‐S3), mean liver stiffness values were significantly higher in subjects with severe steatosis or controlled attenuation parameter ≥287 dB/m compared with those without. Moreover, in subjects with low‐grade fibrosis, a higher rate of false‐positive rate was observed in patients with severe steatosis than those in patients without (F0‐F2: 28.2% vs 9.7%; F0‐F3: 17.0% vs 5.3%), and in patients with CAP≥287 dB/m compared with their counterpart (F0‐F2: 23.7% vs 9.2%; F0‐F3: 14.1% vs 4.8%). Low‐grade fibrosis was accurately identified by γ‐glutamyl transpeptidase‐to‐platelet ratio (GPR) with a cut‐off value of 0.17. In patients with GPR<0.17, similar results were observed. The presence of steatosis may lead to overestimation of fibrosis assessed by liver stiffness measurement in patient with chronic hepatitis B. A diagnostic algorithm for assessing fibrosis using liver stiffness was developed by combining both controlled attenuation parameter and GPR values.